Gender Analysis of Marriage Guardians in the Compilation of Islamic Law - Abd. Rasyid Sidiq; Rusli Rusli; Syahabuddin Syahabuddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
The concept of marriage guardians in Islamic Law Compilation still seems biased and patriarchal, because women do not have the right to marry themselves or others. Articles on guardian of marriage are still less responsive to women's interests. A gender imbalance regarding the concept of marriage guardians is further strengthened by the provisions of marriage guardians in the Islamic Law Compilation which are strictly aimed at men. This research used literature review method based on the Compilation of Islamic Law and gender theory. This study found that, the information about guardian of marriage which is a man’s right from the father's line is actually in line with the pagan Arab culture, including the contribution of Quraish hegemony in interpreting religious propositions. In this regard, Arab societies like Quraish had great respect for a person based on their lineage, so that everyone who was respected would wholeheartedly keep their honor. The lineage in Arabic culture is in the hands of the male lineage, and women are entered into second-class citizens in front of them.